2011
DOI: 10.3109/0886022x.2011.559298
|View full text |Cite
|
Sign up to set email alerts
|

Symmetrical Ambulatory Arterial Stiffness Index: Relationship with Serum Cystatin C Levels

Abstract: Objective: Increased central arterial stiffening is the consequence of many disease states such as diabetes, atherosclerosis, and chronic renal disease. Symmetrical Ambulatory Arterial Stiffness Index (Sym-AASI) may provide a simple clinical approach to evaluate arterial stiffness. This study has tried to evaluate the relationship of Sym-AASI with cystatin C levels. Design and methods: The sample subjects were 53 males and 34 females (mean age = 59.3 ± 13.5 years). Kidney function was evaluated by measuring se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It was found to correlate with pulse pressure (PP) and pulse wave velocity (PWV) and was thus presumed to be another marker of large artery stiffness, which is readily available from ABP. Moreover, one of the most attractive features of AASI was that it was found to be a significant predictor of stroke, cardiovascular disease, renal dysfunction, hypertensive target organ damage, and all‐cause mortality, and, in many of these studies, independently from BP or PP. This independence of BP (or PP) brought about investigations of its possible arterial properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was found to correlate with pulse pressure (PP) and pulse wave velocity (PWV) and was thus presumed to be another marker of large artery stiffness, which is readily available from ABP. Moreover, one of the most attractive features of AASI was that it was found to be a significant predictor of stroke, cardiovascular disease, renal dysfunction, hypertensive target organ damage, and all‐cause mortality, and, in many of these studies, independently from BP or PP. This independence of BP (or PP) brought about investigations of its possible arterial properties.…”
mentioning
confidence: 99%
“…Gavish and colleagues found that some of the problems associated with AASI (for instance its dependence on nocturnal BP decline) can be improved when using a more advanced form of regression of systolic and diastolic BP, the so‐called symmetric regression, which, in this context, provides a slope between that of diastolic on systolic and that of systolic on diastolic BP regression lines. This symmetric AASI (sAASI) has been found to better represent arterial stiffness in patients with HIV, to be associated with cystatin C as a measure of renal dysfunction, and to be associated with estimated glomerular filtration rate and microalbuminureia . Moreover, Gavish and colleagues found that their regression slope was both a mathematic and empiric ratio of the variability of systolic BP over that of diastolic BP, ie, the BP variability ratio (BPVR).…”
mentioning
confidence: 99%